Maintenance management of commercial Complex basement / Mohd Adzzuha Mohd Mansor - Mohd Mansor, Mohd Adzzuha (2009)
The goal of study is to view maintenance management for commercial complex basement that focus on building more than 20 years in Kuala Lumpur and Shah Alam city centre. Within this study, some objectives are formulated: 1. To identify the common problem arising in basement 2. To know the proper maintenance to avoid any serious problem related to structure, security or facilities. 3. to know the performance of management of maintenance in basement This study is limited to maintenance staff in maintenance management for the basement for the all case study. It's also limited to public user which is use the basement for their facilities. The study used a questionnaire survey as a mean of collecting data. Close ended and open ended questionnaire were developed based on the objectives of the research. From my research, it found in overall the old building which have basements have the similar common problem arising at basement. So, the basements should have the good maintenance management in terms of planning, scheduling, coordinating and monitoring to give the long life and can reduce the cost overhead of building.